On being a mentor : a guide for higher education faculty - Johnson, W. Brad; Griffin, Kimberly A. (New York, NY : Routledge, 2025)
This third edition ofthe classic On Being a Mentor is the definitive guide to the art and science of engaging students and faculty in effective mentoring relationships in all academic disciplines. Written for professors and academic leaders with pithy clarity, the text is rooted in the latest research on developmental relationships in higher educational settings and offers concrete mentoring strategies and best practices. On Being a Mentor is infused with an equity-minded approach, and challenges faculty to foster cultures and leverage developmental relationships that honor mentees' identities to promote inclusion, equity, and belonging. The authors couple this call with evidence-based rules of engagement for mentoring--including both relational and career mentoring tactics--as well as methods for forming and managing these relationships. The authors provide mentors with a road map to being ethical and managing relationship problems, and leaders will gain insights into selecting and training mentors, assessing mentorship outcomes, and cultivating a mentoring culture. Chock full of illustrative case-vignettes, reflection questions, and suggested readings, this book is the ideal guidebook for faculty and a comprehensivetraining tool for mentoring workshops. It will be a fantastic volume of reference for graduate students in colleges, universities, and professional schools in all academic fields including the social and behavioral sciences, education, natural sciences, humanities, and business, legal, and medical schools.
Keywords: Mentoring in education -- Handbooks, manuals, etc; College teachers -- Handbooks, manuals, etc; Teaching; PSYCHOLOGY / Education & Training; EDUCATION / Professional Development; EDUCATION / Guidance & Orientation